Physical and Chemical Properties of Cultivated Peat Soils in Four Trial Sites of ICCTF in Kalimantan and Sumatra, Indonesia - Hikmatullah, .; Sukarman, . (UNIVERSITY OF LAMPUNG, 2014)
The large distribution of peat soils in Indonesia have important role in carbon stock and greenhouse gas emission which contribute to global warming issue. The objective of this study was to characterize physical and chemical properties of cultivated peat soils in four trial sites of Indonesia Climate Change Trust Fund (ICCTF) in Central Kalimantan, South Kalimantan, Riau and Jambi Provinces to provide a baseline data by a greenhouse gas emission study. Detailed soil observations were conducted using grid system with spacing of 25 Ã— 50 m. A total of 16 representative peat soil profiles consisting of 74 soil samples of horizons were selected for laboratory analyses. The results showed that peat maturity varied from hemic to sapric in the surface layers and hemic in the subsurface layers, except in Site-2 that was fibric. The peat thickness ranged respectively from 5.4 to 7.0 m in Site-1 and Site-3, and from 0.5 to 2.5 m in site-2 and site-4, and all overlying fine-textured mineral soil (substratum). Depth of water table varied from 10 to 30 cm in Site-2 and Site-4, and from 30 to 70 cm in Site-1 and Site-3. Fiber content ranged from 13 to 57% and increased with depth indicating the peat was less decomposed. The bulk density was very low (0.07-0.24 g cm-3) and negatively correlated to fiber content (r = 0.74 for Kalimantan and r = 0.66 for Sumatra). The ash content was low (0.1-8.5%) and negatively correlated to organic carbon content (r = 0.89 for Kalimantan and r = 0.65 for Sumatra). Soil CEC was high and positively correlated to organic carbon content (r = 0.86 for Kalimantan and r = 0.93 for Sumatra). These soils showed very acid reaction (pH 3.3-4.7), low content of exchangeable bases and total P2O5 and K2O (HCl 25%). Based on these properties, the peat soils were grouped as oligotrophic ombrogenous peat. The estimated carbon stock for all the trial sites with total extent of 22.58 ha was 57,282 Mg C. The variation of thickness, maturity, and water table depth will imply to the magnitude of carbon reserves and greenhouse gas emissions. [How to Cite: Hikmatullah and Sukarman. 2014. Physical and Chemical Properties of Cultivated Peat Soils in Four Trial Sites of ICCTF in Kalimantan and Sumatra, Indonesia. J Trop Soils 19: 131-141. Doi: 10.5400/jts.2014.19.3.131]